New insights into the evolution of human Y chromosome palindromes through mutation and gene conversion - Bonito, Maria; D’Atanasio, Eugenia; Ravasini, Francesco; Cariati, Selene; Finocchio, Andrea; Novelletto, Andrea; Trombetta, Beniamino; Cruciani, Fulvio (Human molecular genetics, 2021)
Abstract About one-quarter of the euchromatic portion of the male-specific region of the human Y chromosome consists of large duplicated sequences that are organized in eight palindromes (termed P1–P8), which undergo arm-to arm gene conversion, a proposed mechanism for maintaining their sequence integrity. Although the relevance of gene conversion in the evolution of palindromic sequences has been profoundly recognized, the dynamic of this mechanism is still nuanced. To shed light into the evolution of these genomic elements, we performed a high-depth (50×) targeted next-generation sequencing of the palindrome P6 in 157 subjects belonging to the most divergent evolutionary lineages of the Y chromosome. We found 118 new paralogous sequence variants, which were placed into the context of a robust Y chromosome phylogeny based on 7240 SNPs of the X-degenerate region. We mapped along the phylogeny 80 gene conversion events that shaped the diversity of P6 arms during recent human history. In contrast to previous studies, we demonstrated that arm-to-arm gene conversion, which occurs at a rate of 6.01 × 10 −6 conversions/base/year, is not biased toward the retention of the ancestral state of sequences. We also found a significantly lower mutation rate of the arms (6.18 × 10−10 mutations/base/year) compared with the spacer (9.16 × 10−10 mutations/base/year), a finding that may explain the observed higher inter-species conservation of arms, without invoking any bias of conversion. Finally, by formally testing the mutation/conversion balance in P6, we found that the arms of this palindrome reached a steady-state equilibrium between mutation and gene conversion.